Inside Back Cover: Facile Synthesis of Hierarchical Nanosized Single‐Crystal Aluminophosphate Molecular Sieves from Highly Homogeneous and Concentrated Precursors (Angew. Chem. Int. Ed. 9/2020). Issue 9 (31st January 2020) - Tao, Shuo; Li, Xiaolei; Wang, Xiaoge; Wei, Ying; Jia, Yunling; Ju, Jing; Cheng, Yuanhui; Wang, Huaisheng; Gong, Shuwen; Yao, Xingjun; Gao, Haixu; Zhang, Cunyin; et al.
Abstract : Nanosized single‐crystal hierarchical aluminophosphate zeotypes of LTA, AEL, AFI, and ‐CLO topologies are synthesized without growth modifiers and mesoporogens, as described by S. Tao, Z. Tian et al. in their Communication on page 3455 . The background of the cover picture is the "Pansi Hole" from the ancient Chinese classic novel "Journey to the West", which represents the interconnected mesoporous structure of the product.